Ajiboy bakery donuts plan report / Muhammad Razif Ali ... [et. al] - Ali, Muhammad Razi; Abdul Aziz Faisal, Mohammad Fathul Azim Faisal; Zulkifli, Muhammad Shafiz Izhar; Kamari, Muhammad Na’im; Ronnie, Juliana; Julin, Tiffaany Menda (2022)
A business plan is a document that identifies, describes, and analyses a business opportunity or an existing business, taking into account the potential's technological, economic, and financial feasibility. The business plan, in particular, lays out all of the procedures and methods that will be used to develop the business possibility into a viable and profitable venture. Having our own business plan, according to Ajiboy Bakery Donuts, will boost the chances of the company growing successfully and profitably. This is because using business planning as a strategy has numerous advantages for every company. The first function of business plans is to allow the business owner to observe and evaluate the company in an objective, critical, and practical manner. This business plan enables the company's management to build a strategy and make more objective, critical, and practical business decisions with ease.